A Thin Felt Mattatore between Industry, Intermediality and Stardom - Martina Zanco (Cinergie)
Michael Twyman argues that “every object tells a story, or at least reveals some information about something” (2008: 25). So what can two puppets made at the end of the 1950s, inspired by the television show Il Mattatore (Daniele D’Anza, 1959) and the likeness of Vittorio Gassman, tell us? In order to recover the complexity of the two toys and to question their possible value in the context of research on the history of cinema, this article proposes to examine them from the point of view of industry, the systemic interrelation between media and the study of stardom.